Implementation of HLA-B*15:02 Genotyping as Standard-of-Care for Reducing Carbamazepine/Oxcarbazepine Induced Cutaneous Adverse Drug Reactions in Thailand - Tiwattanon, Kanyawan; John, Shobana; Koomdee, Napatrupron; Jinda, Pimonpan; Rachanakul, Jiratha; Jantararoungtong, Thawinee; Nuntharadthanaphong, Nutthan; Kloypan, Chiraphat; Biswas, Mohitosh; Boongird, Apisit; Sukasem, Chonlaphat (Frontiers in Pharmacology, 2022)
Objective: This study aimed to investigate the clinical impact of HLA-B*15:02 pharmacogenomics (PGx) testing before carbamazepine (CBZ)/oxcarbazepine (OXC) prescriptions and to determine whether this PGx testing was associated with the reduction of CBZ/OXC-induced cutaneous adverse drug reactions (CADRs) in Thailand. Methods: This retrospective observational cohort study was conducted by obtaining relevant HLA-B*15:02 PGx-testing and clinical data from electronic medical records during 2011–2020. 384 patient data were included in this study to investigate the clinical decision on CBZ/OXC usage before and after the HLA-B*15:02 PGx testing, and 1,539 patient data were included in this study to demonstrate the incidence of CBZ/OXC-induced SCARs and SJS between HLA-B*15:02 tested and non-tested patients. To analyze and summarize the results, descriptive statistics were employed, and Fisher exact test was used to compare the clinical difference between the HLA-B*15:02 positive and negative groups and to compare the differences of SCARs incidence. Results: 384 patients were included in this study as per the inclusion criteria. Of these, 70 patients carried HLA-B*15:02, of which 63 and 65 patients were not prescribed with CBZ/OXC before and after the availability of genotyping results, respectively. In the remaining HLA-B*15:02 non-carriers, 48, and 189 patients were prescribed CBZ/OXC before and after genotyping results were available, respectively. The findings of this study showed that the incidence of SCARs of CBZ/OXC was significantly lower (p < 0.001) in the HLA-B*15:02 screening arm than in the non-screening arm. Conclusion:HLA-B pharmacogenetics testing influenced the selection of appropriate AEDs. The presence of mild rash in the HLA-B*15:02 negative group indicates that other genetic biomarker (HLA-A*31:01) and/or non-genetic variables are involved in CBZ/OXC-induced CADRs, emphasizing that CBZ/OXC prescriptions necessitate CADR monitoring. The hospital policy and clinical decision support (CDS) alert system is essential to overcome the barriers associated with the utilization of PGx guidelines into clinical practice.